TINJAUAN ETIKA BISNIS ISLAM DALAM PENGELOLAAN CORPORATE SOCIAL RESPONSIBILITY - IRSADUNAS IRSADUNAS; YENTI AFRIDA; RAHMI KHAIRANI (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The research objective is to look at business ethics in Islam in the management of Corporate Social Responsibility at PT. Gersindo Minang Plantation. The subject of this research is the sustanability development of the CSR department at PT. Gersindo Minang Planatation and the people who feel the CSR activities. This research is a type of field research. Data collection uses observation, interview, and documentation methods. Data analysis was carried out in a qualitative descriptive manner. The validity of the data using triangulation techniques. The results showed that CSR management at PT. Gersindo Minang Plantation in general, is engaged in education, environment, health and social affairs. There are two types of programs, namely the Patronage and Community Development Program. In terms of Islamic business ethics, of the five axioms that include unity, equilibrium, free will, benevolence and responsibility there is one axiom that is not reflected in the program namely responsibility.